ChemInform Abstract: Solid Lipid Nanoparticle‐Based Calix[n]arenes and Calix‐Resorcinarenes as Building Blocks: Synthesis, Formulation and Characterization. Issue 14 (April 2015) - Montasser, Imed; Shahgaldian, Patrick; Perret, Florent; Coleman, Anthony W.
Abstract: Review: 124 refs.